The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-10323-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of sildenafil and l-arginine in an experimental rat model for the prevention of neonatal necrotizing enterocolitis

Abstract: Necrotizing enterocolitis (NEC) has a 45% mortality in neonatal intensive care units. This paper aimed to evaluate the isolated and combined effects of sildenafil and l-arginine in the prevention of necrotizing enterocolitis. Neonatal rats were fed formula milk and submitted to hypoxia under a 100% N2 atmosphere for 70 s. Then, animals were subjected to hypothermia (4 °C for 10 min), twice a day for 3 days. Forty neonatal rats were divided into five groups: negative control—not submitted to the protocol (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
0
0
Order By: Relevance
“…Formula feeding was also an independent risk factor for NEC in our study. This is consistent with previous research ( 35 ). Chen et al found that formula feeding was strongly associated with intestinal ischemia and hypoxia in human NEC ( 30 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Formula feeding was also an independent risk factor for NEC in our study. This is consistent with previous research ( 35 ). Chen et al found that formula feeding was strongly associated with intestinal ischemia and hypoxia in human NEC ( 30 ).…”
Section: Discussionsupporting
confidence: 94%
“…These conditions can affect the growth and health of newborns. Previous studies have reported that hypothermia in low birth weight premature infants is significantly associated with increased in-hospital mortality and NEC (26)(27)(28)(29). Similarly, our study also found a negative correlation between the body temperature of infants entering the NICU within 24 h after birth and the incidence of NEC, that is, the lower the body temperature of the infant, the greater the probability of developing NEC.…”
Section: Discussionmentioning
confidence: 99%